Vitiligo Adverse Event Observed in a Patient With Durable Complete Response After Nivolumab for Metastatic Renal Cell Carcinoma - Billon, Emilien; Walz, Jochen; Brunelle, Serge; Thomassin, Jeanne; Salem, Naji; Guerin, Mathilde; Vicier, Cecile; Dermeche, Slimane; Albiges, Laurence; Tantot, Florence; Nenan, Soazig; Pignot, Geraldine; et al. (Frontiers in Oncology, 2019)
Background: Renal cell carcinoma is the third most prevalent urological cancer worldwide and about 30% of patients present with metastatic disease at the time of diagnosis. Systemic treatments for metastatic Renal Cell Carcinoma have improved recently. Vascular endothelial growth factor targeting therapies were the previous standard of care. However, immune checkpoint inhibitors used in second line therapy have now been shown to improve patient survival. We report a case of metastatic renal cell carcinoma with nivolumab as a second‐line therapy after progression with tyrosine kinase inhibitor therapy. Unusual adverse events in metastatic renal cell carcinoma, such as vitiligo, were observed in this patient who developed a remarkable documented pathological complete response to his renal tumor. Case presentation: A 60-year-old Caucasian male was diagnosed with a pulmonary metastatic clear cell renal cell carcinoma. Sunitinib was used as first line treatment without success. He received nivolumab in second‐line treatment. He developed several immune-related adverse events, most notably vitiligo. The patient had a radiological complete response on metastatic sites, with a significant decrease of renal tumor volume. and underwent cytoreductive nephrectomy after 2 years of treatment, confirming the pathological complete response. The patient remains disease-free for 10 months without further systemic therapy after nivolumab discontinuation. Conclusions: Pathological complete response with nivolumab in metastatic renal cell carcinoma is rare. This case further highlights the potentially predictive role of immune-related adverse events during nivolumab therapy for metastatic renal cell carcinoma and raises questions concerning the role of nephrectomy after immune checkpoint inhibitor therapy. Further studies are needed to better identify predictive factors for treatment response to immunotherapy in metastatic renal cell carcinoma, and to better understand the role of nephrectomy after nivolumab treatment.